2021
DOI: 10.3389/fped.2021.597870
|View full text |Cite
|
Sign up to set email alerts
|

Lower Leg Fractures in Children and Adolescents—Comparison of Conservative vs. ECMES Treatment

Abstract: Background: Lower leg fractures are one of the most common fractures in pediatric age. In general, treatment of lower leg fractures is predominantly non-operative, requiring clinical and radiological controls. Nevertheless, it can be observed that in recent years tibial shaft fractures have increasingly been treated surgically. The aim of the present study is to investigate treatment strategies in the context of different fracture types of the lower leg.Methods: In this retrospective chart review, we analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
1
5
0
1
Order By: Relevance
“…Post-operative issues increase the length of hospital stay [24], with significant financial relevance and patients' mental and health well-being issues, especially in children. Patients' length of stay in this series (both casting and surgery) is comparable to the results reported by Weber et al [9].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Post-operative issues increase the length of hospital stay [24], with significant financial relevance and patients' mental and health well-being issues, especially in children. Patients' length of stay in this series (both casting and surgery) is comparable to the results reported by Weber et al [9].…”
Section: Discussionsupporting
confidence: 88%
“…However, surgical management is sometimes appropriate based on patient characteristics and fracture patterns [7]. Improvement and innovation in surgical techniques, a drive to reduce hospital stays and early mobilization for rehabilitation are also factors influencing surgical decisions [8,9]. This study's objective is primarily to evaluate the management of displaced tibia shaft and metaphyseal fractures in children.…”
Section: Introductionmentioning
confidence: 99%
“…Weber et al 44 reported that, among 168 tibia fractures in children treated in the emergency room between 2005 and 2017, 38 were surgically treated, 36 of which were fixed with flexible rods or plate and two stabilized with external fixator. The mean age of the patients treated conservatively was statistically lower (6 years old) when compared to that of the operated patients (10.2 years old).…”
Section: Literature Datamentioning
confidence: 99%
“…Both bones are broken in 30% of patients, and isolated fibular fractures are rare [ 3 ]. According to the type, the transverse or short oblique fractures of the tibia are most commonly seen [ 4 , 5 ]. The tibia is most susceptible to trauma in the area of transition from the middle to the distal third due to anatomical changes in the cross-section of the bone from triangular to round in shape [ 6 ].…”
Section: Introductionmentioning
confidence: 99%